Political donations and political risk in the UK: Evidence from a closely-fought election - Acker, Daniella; Orujov, Ayan; Simpson, Helen (Journal of Banking & Finance, 2018)
UK regulation discourages corporate political donations but is relatively benign in respect of individual donations. Few UK listed companies make political donations but many more company directors do. We use a unique, hand-collected dataset of political donations to examine whether UK corporate political connections are perceived as being created indirectly via directors’ personal donations. Basing our tests on the sensitivity of company returns to opinion polls preceding the 2010 General Election we find that, on average, firms in industries which donate only to the Conservative Party exhibit higher sensitivity to the electoral success of the Conservatives. However, within industries, there is no consistent evidence that the firms which employ directors who make these donations exhibit higher sensitivity than firms which do not. We justify basing our inferences on return sensitivity to polls by confirming that UK domestic political risk, as proxied by opinion poll changes, is priced around General Elections.